2010
DOI: 10.1111/j.1475-6773.2010.01115.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of the WIC Program on the Health of Newborns

Abstract: Overall, the WIC program had moderate effects, but findings were sensitive to the estimation method used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 48 publications
0
32
0
1
Order By: Relevance
“…77,78 Limited research has examined health-care utilization among program participants. 79 Several studies in the general population have found equivocal 80,81 or detrimental 82 health outcomes associated with program participation; these studies are difficult to interpret because selection bias was probably not at all or only partially controlled.…”
Section: Discussionmentioning
confidence: 99%
“…77,78 Limited research has examined health-care utilization among program participants. 79 Several studies in the general population have found equivocal 80,81 or detrimental 82 health outcomes associated with program participation; these studies are difficult to interpret because selection bias was probably not at all or only partially controlled.…”
Section: Discussionmentioning
confidence: 99%
“…Pregnant women and their young children who participate in WIC have higher nutrient intake than their similar peers who do not, based on both observational and experimental study designs (Fox, Hamilton and Lin 2004; Metcoff et al 1985; Rush et al 1988). In addition, mothers who participate in WIC are more likely to have babies with a healthy birthweight, an important indicator of fetal growth and maternal nutrition (Bitler and Currie 2005, Foster, Jiang and Gibson-Davis 2010; Kowaleski-Jones and Duncan 2002; Owen and Owen 1997; Rossin-Slater 2013). A parallel body of research documents the relationships among nutrition, cognitive development and academic achievement around the world, whether measured by irondeficiency anemia, height, or policy participation (Behrman et al 2009; Glewwe and King 2001).…”
Section: Introductionmentioning
confidence: 99%
“…The greater socioeconomic disadvantage of WIC enrollees compared to both the ineligible population, and potentially the eligible population who does not enroll, means that there is a substantial correlation between socioeconomic measures and both WIC participation and children’s outcomes (Bitler and Currie 2005; Kowaleski-Jones and Duncan 2002). An increasingly common approach to examining the effects of WIC is to use statistical techniques well-suited to address the problem of non-random selection into the program, including fixed-effects models and matching approaches (Foster, Jiang and Gibson-Davis 2010; Rossin-Slater 2013). In this study, I use coarsened exact matching to thoroughly control for observable characteristics associated with the probability of participating in WIC, generating “treatment” and “control” groups that have highly similar empirical distributions on observed variables.…”
Section: Introductionmentioning
confidence: 99%
“…Our analysis by trimester of WIC enrollment is consistent with other studies that have shown a dose---response relationship with WIC prenatal participation and infant birth weight. 17,27,29,31 A second strength is that infant's length and weight were measured according to standard protocols by trained WIC staff or came from medical referral. Heights and lengths and weights measured by trained staff in WIC settings have been shown to be highly reliable and valid for research purposes.…”
Section: Discussionmentioning
confidence: 99%